Pragmatics of fiction - Locher, Miriam A.; Jucker, Andreas H. (Handbooks of pragmatics, 2017)
Pragmatics of Fiction provides systematic orientation in the emerging field of studying pragmatics with/in fictional data. It provides an authoritative and accessible overview of this versatile new field in its methodological and theoretical richness. Giving center stage to fictional language allows scholars to review key concepts in sociolinguistics such as genre, style, voice, stance, dialogue, participation structure or features of orality and literariness. The contributors explore language as one of the creative tools to craft story worlds and characters by drawing on concepts such as regional, social and ethnic language variation, as well as multilingualism. Themes such as emotion, taboo language or impoliteness in fiction receive attention just as the challenges of translation and dubbing, the creation of past and future languages, the impact of fictional language on language change or the fuzzy boundaries of narratives. Each contribution, written by a leading specialist, gives a succinct, representative and up-to-date overview of research questions, theories, methods and recent developments in the field.
Keywords: Pragmatik; Textanalyse; Prosa